78 Impact of Ethnicity on Mortality Amongst Tobacco Abusers in the United Kingdom. (3rd June 2016) - Carter, Paul R; Reynolds, Jennifer; Carter, Andrew; Uppal, Hardeep; Chandran, Suresh; Sarma, Jaydeep; Potluri, Rahul
Abstract : Introduction: Tobacco smoking contributes significantly to the global health burden and its negative impact on cardiovascular morbidity and mortality in particular have been well documented. Smoking is affected by sociodemographic factors though with rates varying according to sex, social class and ethnicity. However, the impact of ethnicity on mortality amongst hospitalised tobacco abusers is yet to be studied. Objectives: We aimed to investigate the impact of ethnicity on mortality of hospitalised patients with a comorbid diagnosis of tobacco abuse. We did this using a large database of patients admitted with comorbid tobacco abuse to hospitals in the North of England between 2000–2013. Methods: Anonymous information on adult tobacco abusers was obtained for hospitals in North West England between 1 st January 2000 and 31 st March 2013. This data was analysed according to the ACALM (Algorithm for Comorbidities, Associations, Length of stay and Mortality) study protocol. ICD-10 and OPCS-4 codes were used to trace patients coded for tobacco abuse, patient demographics and mortality data. Mortality of tobacco abuse patients was compared by logistic regression. P values of <0.05 were taken as statistically significant. Results: 28379 patients had comorbid tobacco abuse during the study period. Mean age of tobacco abusers was 44.9 years, 51.2% were male and 1918 (6.8%) tobacco abuse patients died. The majority were Caucasian (84.8%) with lower proportions of South Asian (4.7%), Afro-Caribbean (1.9%), Oriental (0.2%), mixed (1.0%), other (2.5%) and unknown (4.8%) ethnicities. Crude mortality was highest amongst Caucasian patients (7.3%) compared to South Asian (2.2%), Afro-Caribbean (2.7%), Oriental (1.7%), mixed (0.3%), other (3.1%) and patients with unknown ethnicities (6.1%). Of all these ethnic groups, logistic regression accounting for age and sex showed that only South Asian ethnic origin affected mortality rates amongst patients with comorbid tobacco abuse. South Asian patients were 1.90 times more likely to die (95% CI 1.21–2.97). Conclusion: Our results demonstrate that mortality of tobacco abusers varies according to ethnicity with higher mortality amongst South Asian patients in particular. This could represent differences in smoking rates or an increased susceptibility to smoking. This is particularly important given that smoking and South Asian ethnicity are both known risk factors for developing cardiovascular disease.